Value Engineering for the Role of Internal Audit Quality in Activating the Principles of Corporate Governance: A Case of Non-financial Firms on Iraqi Stock Exchange - Hassan Sabbar, Mohammed; Eltyaf Abdalamer, Safa (International Journal of Engineering and Technology, 2018)
The main purpose of this study is to investigate the impact of the quality of internal audit on the effectiveness of corporate governance in Iraqi listed firms. The frequency of audit committee meeting and board size are in a negative and significant relationship of the audit committee and firm size are only variables which in negative relation with corporate governance index. Whereas all the other variables which independence of audit committee are, qualification if independent director in audit committee and audit committee to board independence are in positive relation to corporate governance. The results indicate that along with independence its mandatory to have qualified person on a board committee. Similarly, the frequency of audit committee also appears in positive relation to corporate governance practices for the sample of Iraqi firm. The results of the study provide support with agency theory. This study will be helpful for policymakers and corporate heads in formulating policies related to development and implementation of corporate governance.Â Â